Association of Melanocortin 4 Receptor gene polymorphism with growth traits in Bligon goat - Latifah, L.; Maharani, D.; Kustantinah, A.; Hartatik, T. (Diponegoro University, 2018)
Melanocortin 4 receptor gene is a potential marker gene for growth performance in ruminant and non-ruminant animals. The objective of this study was to perform allele and genotype frequencies, and association of melanocortin 4 receptor with growth traits in Bligon goat. Seventy seven blood samples were collected and DNA isolated successfully. One pair primers were used for PCR of MC4R gene (F: 5’-TCGGGCGTCTTGTTCATCAT-3’ and R: 5’-CAAGACTGGGCACTGCTTCA-3’). Two SNPs (g.998A/G and g.1079C/T) were identified in exon of Bligon MC4R by DNA sequencing and PCR-RFLP. The SNP g.998A/G identified amino acid change from isoleucine to methionine (I-M), while the SNP g.1079C/T was synonymous polymorphism. Based on relationship analysis between Genotype of MC4R gene (SNP g.998A/G) and growth traits indicated that GG genotype was lowest in weaning weight (WW; AA=13.0±1.7; AG=11.2±3.6; GG=9.2±3.9), weaning body length (WBL; AA=46.8±2.4; AG=46.3±6.0; GG=43.8±5.3) and weaning chest circumference (WCC; AA=50.9±4.0; AG=50.7±4.6; GG=47.1±7.3) compare to AA and AG genotype (p<0.05). Individual with CC and CT genotypes at SNP g.1079C/T had higher (P<0.05) in WW (CC=12.6±2.1; CT=12.5±2.5) and average daily gain (ADG; CC=81.2±21.8; CT=79.3±26.2) than TT genotype (WW=10.6±3.1; ADG=58.3±30.5). This results suggested that SNP g.998A/G and g.1079C/T of MC4R gene could be used as the genetic marker of growth traits for selection in Bligon goat.